(untitled) (Rainbow Journal, 2019)
This study is related to the use of the tool of self-efficacy beliefs in teaching mathematics through using history of mathematics, based on Self-efficacy Theory of Bandura (1977). The instrument is adapted from Enoch, Smith and Huinker’s (2000) instrument which contains 21 statements grouped into two dimensions of self-efficacy beliefs: personal mathematics teaching efficacy (PMTE) and mathematics teaching outcome expectancy (MTOE). Exploratory factor analysis was employed to maintain construct validity; and reliability was maintained by Cronbach alpha (α = .829, N = 305) to assess internal consistency of the items. Pre-service mathematics teachers’ self-efficacy beliefs can be increased through the use of this tool.